Naltrexone blocks endorphins released when dancing in synchrony - Tarr, B; Launay, J; Benson, C; Dunbar, R (Springer, 2017)
Group synchronised dance is hypothesised to activate the Endogenous Opioid System (EOS), thereby increasing pain threshold, and encouraging social closeness. Previous studies have been limited to the use of pain threshold as a proxy indicator of EOS activation. We conducted a double-blind administration of placebo and naltrexone (an endorphin antagonist) before groups of strangers danced in synchrony and measured both pain threshold and sense of belonging to the group after dancing. A 100 mg dose of naltrexone resulted in significant hyperalgesic effects compared to the control participants, confirming that increases in pain threshold in the control group are due to activation of the EOS and release of endorphins during synchronised dancing. However, there was no significant effect of treatment on perceptions of social closeness. Social bonding during dance may plausibly be underpinned by elements of the EOS not blocked by naltrexone and/or interactions with other neurohormones and socio-cognitive mechanisms.